2004
DOI: 10.1016/j.biocontrol.2003.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Habitat manipulation of the apple orchard floor to increase ground-dwelling predators and predation of Cydia pomonella (L.) (Lepidoptera: Tortricidae)

Abstract: Augmenting generalist predator populations in new apple (Malus domestica Bork) plantings could potentially aid in the establishment of balanced orchard ecosystems that are less susceptible to pest outbreaks. Habitat can be an important factor in retaining predators in a system and can affect predator efficiency. We investigated the potential of increasing a complex of generalist ground-dwelling predators and enhancing biological control in a young ÔGolden DeliciousÕ apple orchard through ground habitat manipul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 52 publications
3
68
0
4
Order By: Relevance
“…We assessed ant predatory impact by examining removal rates of two sentinel prey items, frozen (and presumed dead) West Indian fruit flies (Anastrepha obliqua Macquart) and coffee berry borers that were added to forest and coffee sites. In many studies with sentinel prey, prey items are restricted from moving by being glued (Armbrecht and Perfecto, 2003) or tethered (Jedlicka et al, 2011;Mathews et al, 2004) to observation locations. Other studies restrict prey movement by using frozen (and thus dead) prey items (e.g., Gardiner et al, 2014;Jones et al, 2001;O'Neal et al, 2005;Prasifka et al, 2006).…”
Section: Predation Trialsmentioning
confidence: 99%
“…We assessed ant predatory impact by examining removal rates of two sentinel prey items, frozen (and presumed dead) West Indian fruit flies (Anastrepha obliqua Macquart) and coffee berry borers that were added to forest and coffee sites. In many studies with sentinel prey, prey items are restricted from moving by being glued (Armbrecht and Perfecto, 2003) or tethered (Jedlicka et al, 2011;Mathews et al, 2004) to observation locations. Other studies restrict prey movement by using frozen (and thus dead) prey items (e.g., Gardiner et al, 2014;Jones et al, 2001;O'Neal et al, 2005;Prasifka et al, 2006).…”
Section: Predation Trialsmentioning
confidence: 99%
“…The number of captures recorded with synthetic cover (T2) may be due to this inert material providing less availability of alternative food (such as saprophytes) for generalist predators such as the carabids (Ceccanti et al, 2007). In agreement with this interpretation, Mathews et al, (2004) demonstrated that plastic cover significantly reduced the availability of alternative food for the complex of soil predators present in an apple orchard, while a cover of compost, high in organic matter, favored the presence of both alternative prey and predators. Similarly, working with spiders, Birkhofer et al (2008) showed that the presence of organic matter triggered an increment in the availability of alternative prey (mainly dipteran larvae) and that this produced an increase in spider abundance and their control over aphids in wheat.…”
Section: Discussionmentioning
confidence: 68%
“…According to Mathews et al (2004), complex structures composed of plant remains are capable of providing adequate safe sites from other predators, which also protect the carabids from direct exposure to sunlight, resulting in increase in prey capture compared to those recorded using more simple structures. In this case the synthetic cover (T2) is a simple structure, while the cover with pine needles is more complex, thus the microclimatic conditions generated in these structures may explain the differences observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Candidate plants include small trees, shrubs, bushy perennials, and tall ornamental grasses with dense canopies or complex architecture. Similarly, organic mulches and ground cover plants can support large numbers of ground-dwelling predators like spiders and ground beetles (Bell et al, 2002;Mathews et al, 2004;Rieux et al, 1999;Snodgrass & Stadelbacher, 1989), which may enhance biological control of key pests (Brust, 1994). Finally, resource plants can enhance reproduction of natural enemies and provide refuge from their own enemies (Landis et al, 2000;Rabb et al, 1976).…”
Section: Conserving Natural Enemies Via Habitat Manipulationmentioning
confidence: 99%